2017
DOI: 10.1111/phen.12223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of parental RNA interference of a transformer‐2 homologue on female reproduction and offspring sex determination in Asian citrus psyllid

Abstract: Abstract. Asian citrus psyllid Diaphorina citri Kuwayama is the vector of CandidatusLiberibacter asiaticus (CLas), the causal agent of citrus huanglongbing (HLB). A comprehensive understanding of molecular components that govern key physiological traits in D. citri would promote the development of novel genetic control strategies to fight this pest. In the present study, a transformer 2 homologue (Dctra-2) implicated in embryonic sex differentiation in dipteran insects is targeted to interfere with the offspri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Foliar application of actin‐dsRNA is reported to protect potato plants for almost 1 month and shows that the dsRNA is not easily washed off after drying (San Miguel & Scott, ). Notably, parental RNAi effects are observed in the D. citri offspring born from females exposed to dsRNA‐ Dctra‐2 (Yu & Killiny, ). This persistent RNAi effect in D. citri would further enhance the potential applications of RNAi strategy in agriculture.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Foliar application of actin‐dsRNA is reported to protect potato plants for almost 1 month and shows that the dsRNA is not easily washed off after drying (San Miguel & Scott, ). Notably, parental RNAi effects are observed in the D. citri offspring born from females exposed to dsRNA‐ Dctra‐2 (Yu & Killiny, ). This persistent RNAi effect in D. citri would further enhance the potential applications of RNAi strategy in agriculture.…”
Section: Discussionmentioning
confidence: 98%
“…RNAi efficacy in D. citri usually varies with the dsRNA delivery method and type of target genes, as well as the length and concentration of dsRNA fragment. Compared with the high levels of silencing reported in other research after the application of low amounts of dsRNA or even by the in planta system (Taning et al ., ; Andrade & Hunter, ; Yu et al ., ; Yu & Killiny, ), the present study shows that a robust RNAi is observed until feeding on 200 ng μL −1 of ds DcBol . Therefore, for each target gene of D. citri , an optimal concentration should be independently determined to achieve an efficient and optimal silencing effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were some specific studies into the role of parental RNAi in hemipteran insects. It was reported that parental RNAi of Dctra‐2 has a great influence on female fecundity and egg hatchability in Diaphorina citri (Yu & Killiny, ). It was also found that offspring wing morphs can be influenced by the maternal RNAi of the NlTra‐2 gene in a sex‐specific manner in N. lugens (Zhuo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot of 150 μL of the diet was placed between two layers of stretched Parafilm membrane on the 9‐dram clear plastic vial (No. 55‐9; Thornton Plastics Co., Salt Lake City, Utah), with a hole (diameter 0.5 mm) on the side for air ventilation (Yu & Killiny, , b). Concentration, filtration and digestion procedures of soluble saliva were modified from that described previously by Carolan et al .…”
Section: Methodsmentioning
confidence: 99%